Influence of cutting direction of cork planks on the quality and porosity characteristics of natural cork stoppers - Costa, A.; Pereira, H. (Forest Systems, 2010)
In the industrial production of natural cork stoppers, cork planks are cut transversely into strips and stoppers arebored in the axial direction, therefore with their cylinder axis parallel to the tree axial direction. The influence ofcutting direction of cork planks (transverse or longitudinal), and therefore the orientation of stoppers cylindrical axis (longitudinal or tangential, respectively) on yields, quality profile and porosity characteristics was studied in a random sampling of planks of different quality classes that were bored to produce 45 mm × 24 mm stoppers. The stoppers quality profile and production values were not influenced by the cutting direction, although in good quality planks (1st/2nd) the longitudinal cut led to a higher proportion of good quality stoppers in comparison to the transversal cut, 32% vs. 23%. Regarding porosity characteristics, pore orientation differed between the two cutting directions but not the porosity coefficient, with the exception of the poor quality classes.